Root Cause Analysis on Failure of Thermowell - Lee, Agnes Wan Wan (2018)
Thermowell, although small, is an equipment compulsory in the oil and gas industry. This equipment acts as an external protector for temperature taking equipment in process pipelines, which is crucial in attempt to maintain desired temperature in pipeline for quality control of transported medium. This causes the thermowell to be prone to several kinds of failures due to forces, such as frequency limit condition, steady-state stress criterion, fatigue stress limit, and external pressure criterion. A study for this paper is conducted based on existing real-time loss of primary containment case: a straight shank thermowell, which was installed in Multi Purpose Pipeline area in Hengyuan Refining Company (Sdn. Bhd.), Negeri Sembilan area where jet fuel is transported in a pipeline, underwent failure causing leak of medium. The objectives are to analyze root cause of failure that thermowells may undergo and to propose a suitable solution to failures of thermowells. The cracked thermowell by Hengyuan is retrieved from site before analyzation is done based on fault tree analysis depending on site walk, ASME standard for thermowells: PTC 19.3 TW-2010, as well as Vicker‟s Hardness Test to analyze the hardness property on surface of thermowell. Result proves that the thermowell failed due to excessive length, 0.353m. Vicker‟s Hardness Test has also proven that the hardness around the crack of thermowell on surface is less than that of the normal area on surface, which are 201.7 and 199.8 as respectively compared to 221.3 and 203.